Normothermic ex vivo perfusion of isolated lungs in an experiment using a russian-made perfusion system - S. V. Gautier; O. M. Tsirulnikova; I. V. Pashkov; D. O. Oleshkevich; I. A. Filatov; V. K. Bogdanov; D. M. Bondarenko; N. P. Mozheiko; A. A. Karpov; N. S. Bunenkov; N. V. Grudinin (Вестник трансплантологии и искусственных органов)
According to global health statistics, respiratory diseases, together with infectious complications and hereditary lung diseases, rank as the third leading cause of death. Today, lung transplantation (LTx) is a well-recognized modality of treatment for end-stage chronic lung disease. However, the number of LTx surgeries performed is much lower than other solid organs. This is due to the high requirements for the potential donor and characteristics of the lung graft, reflecting the efficiency of gas exchange function. Non-compliance with the selection criteria leads to deselection of donors, which, according to various estimates, occurs in 80–85% of cases. One of the ways to increase the number of lung transplant surgeries is to restore them to the level of optimal gas exchange parameters, which can be achieved and objectively assessed during normothermic ex vivo lung perfusion (EVLP). EVLP is becoming increasingly common at leading transplantation centers in Europe and North America. This has significantly increased the number of transplant surgeries as a result of using lungs procured from suboptimal donors and rehabilitated via EVLP. In our pilot study, the developed Russian-made mechanical circulatory support system showed that performing normothermic EVLP for isolated lungs under experimental conditions is feasible. Basic and optimized perfusion protocols have fully shown that they are reliable and efficient.